2012
DOI: 10.4103/0301-4738.94049
|View full text |Cite
|
Sign up to set email alerts
|

Retinal arterial occlusions in the young: Systemic associations in Indian population

Abstract: Purpose:To determine the systemic associations in retinal arterial occlusions (RAO) in young Indian individuals less than 40 years of age.Materials and Methods:Case records of 32 patients (35 eyes) of less than 40 years, with non-traumatic RAO were analysed. All patients underwent detailed ophthalmic and systemic evaluation including hemogram, lipid profile, coagulation profile, vasculitis screening, carotid Doppler, echocardiogram.Results:In the study 21 were males and 11 were females. The age ranged from 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
1
40
1
Order By: Relevance
“…Frequent etiologies include hypercoagulable states, hyperhomocysteinemia, vasculitis, emboli from cardiac valvular disease, and other risk factors such as smoking, use of oral contraceptives, and vasospasm such as in a history of migraine [2][3][4][5][6][7] . There are few published reports of retinal artery occlusion associated with hyperhomocysteinemia in children [7][8][9] . Abnormal accumulation of homocysteine in plasma, as found in this inborn error of metabolism of the amino acid methionine, also has a toxic effect on endothelial cells resulting in arteriosclerosis, and arterial and venous thromboembolic events at a young age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent etiologies include hypercoagulable states, hyperhomocysteinemia, vasculitis, emboli from cardiac valvular disease, and other risk factors such as smoking, use of oral contraceptives, and vasospasm such as in a history of migraine [2][3][4][5][6][7] . There are few published reports of retinal artery occlusion associated with hyperhomocysteinemia in children [7][8][9] . Abnormal accumulation of homocysteine in plasma, as found in this inborn error of metabolism of the amino acid methionine, also has a toxic effect on endothelial cells resulting in arteriosclerosis, and arterial and venous thromboembolic events at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in the plasma homocysteine concentration can occur because of genetic defects in the enzymes involved in homocysteine metabolism, nutritional deficiencies in vitamin cofactors (folate, vitamin B6, or vitamin B12), or other factors including some chronic medical conditions and drugs. Ratra and Dhupper suggested that the common systemic association of retinal artery occlusion in the Indian population was hyperhomocysteinemia 8 . Karth et al described a previously healthy 7-week-old boy who developed bilateral central retinal artery occlusion in the presence of hyperhomocysteinemia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Central artery occlusions have visual loss which is central and dense. Branch artery occlusions involve sections of the peripheral visual field which may go unnoticed [32,33]. Central Retinal vein occlusion may present as a dense central scotoma with subtle intermittent episodes of blurred vision or it may be a sudden, painless monocular vision loss.…”
Section: Retinal Artery or Vein Occlusionsmentioning
confidence: 99%
“…Elevated homocysteine levels have also been described as an independent risk factor for retinal vascular occlusions especially in young individuals of Indian origin. 5,6 To the best of our knowledge, presence of APS with hyperhomocysteinemia presenting with BRAO as its initial manifestation has not been described previously.…”
mentioning
confidence: 92%
“…4 Other mechanisms include exogenous emboli, thrombotic, vasospastic and vasculitic events. 4,5 We present the case of a young girl who presented with branch retinal artery occlusion. These conditions may occur alone or in combination with each other.…”
mentioning
confidence: 99%